The South American monsoon variability over the last millennium in climate models (2016)
RESUMEN: In this paper we assess South American monsoon system (SAMS) variability in the last millennium as depicted by global coupled climate model simulations. Highresolution proxy records for the South American monsoon over this period show a coherent regional picture of a weak monsoon during the Medieval Climate Anomaly and a stronger monsoon during the Little Ice Age (LIA). Due to the small external forcing during the past 1000 years, model simulations do not show very strong temperature anomalies over these two specific periods, which in turn do not translate into clear precipitation anomalies, in contrast with the rainfall reconstructions in South America. Therefore, we used an ad hoc definition of these two periods for each model simulation in order to account for model-specific signals. Thereby, several coherent large-scale atmospheric circulation anomalies are identified. The models feature a stronger monsoon during the LIA associated with (i) an enhancement of the rising motion in the SAMS domain in austral summer; (ii) a stronger monsoon-related upper-tropospheric anticyclone; (iii) activation of the South American dipole, which results in a poleward shift of the South Atlantic Convergence Zone; and (iv) a weaker upper-level subtropical jet over South America. The diagnosed changes provide important insights into the mechanisms of these climate anomalies over South America during the past millennium.